Development and validation of an RP-HPLC method for simultaneous determination of curcumin and metronidazole in combined dosage form - Pozharani, Leyla Beba; Burgaz, Emine Vildan; Baloglu, Esra (Istanbul Univ, Fac Pharmacy, 2022)
Background and Aims: The present study aimed to develop and validate a simple reverse phase-high pressure liquid chro-matography (RP-HPLC) method for simultaneous determination of natural compound curcumin and metronidazole in bulk and its combined dosage form.Methods: In situ gel formulation containing curcumin and metronidazole was prepared as a model combined system. The chromatographic separation was accomplished isocratically on Eclipse XDB-C18 (150 mm x 4.6 mm, 5 pm particle size) col-umn using UV-detection at 254 nm. The optimized mobile phase contained a mixture of Phosphate Buffer pH4.5-Acetonitrile (50:50, v/v), and the flow rate was set to 1.0 mL/min with 10 pL injection volume. The method was validated in compliance with International Council for Harmonisation (ICH) standards, and it was successfully used for quality control assays for their combined drug productResults: The results for retention times were 8.60 and 1.40 min for curcumin and metronidazole, respectively. The method indicated linear responses within the concentration ranges of 3.0-80 and 4.8-128 pg/mL with LOD values of 0.62; 1.03 pg/mL and LOQ values of 1.88; 3.13 pg/mL for curcumin and metronidazole, respectively. Precision results were within acceptable limits (RSD<2%), and the determination of the two active substances was not interfered with by any formulation components.Conclusion: The proposed validated RP-HPLC method was successfully applied to determine the total contents of curcumin and metronidazole in situ gel formulation. The validation results showed that the proposed method was simple, specific, and precise, and that it could be used for routine quality control for their combined pharmaceutical application.
Keywords: Curcumin; Metronidazole; Simultaneous-quantification; HPLC method development